2005
DOI: 10.4314/jcmphc.v16i1.32405
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Age at BCG administration during routine immunization

Abstract: SummaryIn Nigeria, as part of the National Programme on Immunization (NPI), BCG should be given at birth. A survey of the ages at which mothers bring their children for BCG vaccination showed that only 22% of children receive their BCG within the first 3 days of life and 36.2% within the first 7 days of life. The place of birth and whether a child was sick enough at birth to require hospital admission appears to be an important factor affecting the age at BCG administration Introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The safety of pregnant women and their babies depends on the success of the programme. Wammanda et al (2011) reported that only 22% of children receive their BCG within the first 3 days of life and 36.2% within the first 7 days of life. Adeiga et al (2005) indicated that reasons for failure to immunize or complete the immunization of children included poor knowledge of immunization and belief about immunization in 47%, lack of information in 40.7% and lack of motivation in 11.6%, and only 11% of the children in their study were not vaccinated against measles in the Lagos metropolis.…”
Section: Introductionmentioning
confidence: 99%
“…The safety of pregnant women and their babies depends on the success of the programme. Wammanda et al (2011) reported that only 22% of children receive their BCG within the first 3 days of life and 36.2% within the first 7 days of life. Adeiga et al (2005) indicated that reasons for failure to immunize or complete the immunization of children included poor knowledge of immunization and belief about immunization in 47%, lack of information in 40.7% and lack of motivation in 11.6%, and only 11% of the children in their study were not vaccinated against measles in the Lagos metropolis.…”
Section: Introductionmentioning
confidence: 99%
“…27 Selain itu, untuk mencegah anak terinfeksi TB sebelum pemberian imunisasi BCG, maka anak yang kontak erat bersama penderita TB harus dilakukan imunisasi segera yaitu sebelum anak berusia 7 hari. 31,32 Masih terdapat banyak perdebatan mengenai waktu pemberian imunisasi BCG. Para peneliti menyimpulkan bahwa imunisasi BCG harus diberikan pada anak usia 3 hari, sedangkan peneliti lainnya menyatakan pada usia 3 bulan, anak baru dapat diberikan imunisasi BCG karena pada anak berusia kurang dari 1 bulan belum terbentuk sistem antibodi yang optimal.…”
Section: Bahasanunclassified
“…A study in Northern Nigeria reported a 95.1% prevalence of scar formation. 7 This study however, evaluated only 41 children. Another study in Northern Nigeria evaluated 296 children between the ages of 3 -59months receiving immunization in a Teaching Hospital and two Primary Health Centers.…”
Section: Introductionmentioning
confidence: 99%